2019
DOI: 10.1111/acer.14112
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking and the Risk of Chronic Kidney Damage: A Meta‐Analysis of 15 Prospective Cohort Studies

Abstract: The relationship between alcohol drinking and chronic kidney damage, mainly including declined glomerular filtration rate (GFR), proteinuria, and end-stage renal disease, was conflicting. Thus, a meta-analysis was conducted to investigate their potential associations. PubMed and Web of Science were searched to identify prospective studies assessing the associations between alcohol drinking and chronic kidney damage published up to March 2019. Random-effects model was employed to pool the relative risks (RR) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…To establish a prevention program against CKD, modifiable lifestyle risk factors for CKD should be identified and effective interventions for these defined. Some of the lifestyle risk factors that could be used as promising targets for CKD prevention include obesity [7], smoking [8,9], alcohol consumption [10,11], sleep deprivation [12,13], and unhealthy diet [14].…”
Section: Introductionmentioning
confidence: 99%
“…To establish a prevention program against CKD, modifiable lifestyle risk factors for CKD should be identified and effective interventions for these defined. Some of the lifestyle risk factors that could be used as promising targets for CKD prevention include obesity [7], smoking [8,9], alcohol consumption [10,11], sleep deprivation [12,13], and unhealthy diet [14].…”
Section: Introductionmentioning
confidence: 99%
“…High alcohol consumption was associated with an increased risk of completes suicide ( 58 ) ( Figure 5 ). For chronic kidney damage ( 23 ), the low, moderate and high alcohol consumption were all correlated to reduce the incidence ( Figures 3 – 5 ). What's more, moderate alcohol consumption was found to strongly decrease the risk of frailty ( 21 ) in this study ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have shown that compared with no drinking, regular and occasional binge drinking were associated with 2.2-fold and a 2.0-fold higher risks of CKD progression, respectively. This association was particularly evident in patients who had decreased kidney function and proteinuria [ 38 , 39 ]. In addition, we also found a significant correlation between previous CKD and D-AKI (adjusted OR = 2.33, 95% CI: 1.07-5.08, P = 0.033).…”
Section: Discussionmentioning
confidence: 99%